How Behavior and Perceptions Shape the Use of Digital Wallets in Indonesia - Radiany, M. Andri; Amelia; Purwanto, Nuri (Public Policy, 2025)
This study examines the influence of facilitating conditions, hedonic motivation, price value, and habit on behavioral intention, and the subsequent impact of behavioral intention on actual usage of the DANA digital payment platform in Indonesia. A quantitative method was used, involving 130 respondents who completed a structured online questionnaire. Multiple linear regression analysis revealed that all four variables significantly affect behavioral intention, with habit as the strongest contributor, followed by hedonic motivation, facilitating conditions, and price value. Additionally, behavioral intention was found to have a significant influence on actual usage of DANA. These results highlight that users’ adoption and continued use of digital payment services are strongly shaped by habitual patterns, user enjoyment, and practical benefits such as ease of use and cost efficiency. This study offers valuable insights for service providers aiming to improve user engagement and platform usage.